Clinical characteristics of the digestive system in COVID-19 cases - Febres Ramos, Richard (2022)
At the beginning of the COVID-19 pandemic, digestive problems were not evident among patients suffering from the initial disease in Wuhan, China: only 2.6 % had diarrhea and 2 % chronic liver disease.The virus enters the cells through the receptors of the angiotensin-converting enzyme 2 (ACE2). Recent studies have shown that the ACE2 receptor (which mainly regulates the intestinal flora) is essential for COVID-19-infected cells and is highly expressed not only in the AT2 cells but also in the enterocytes of the ileum and colon. These results confirmed that the gastrointestinal tract may be a potential route for COVID-19 infection.A bibliographic search, which consisted of a review of biomedical literature from MEDLINE, life science journals and online sources on gastrointestinal manifestations during COVID-19 infection, was carried out in PubMed.It is concluded that gastrointestinal manifestations occur during COVID-19 infection, so it is important to know them for providing a timely treatment.